Rå kunst - outsider art i Norge - Rossner, Simone (Sør-Troms Museum, 2014)
This catalogue is published in conjunction with the exhibition "Rå kunst- outsider art i Norge", Galleri NordNorge / Gallery NorthNorway, Harstad, 20.09.2014-18.10.2014. - A total of 100 works by 16 artists are presented, many of them for the first time.